Using peripersonal warning signals to orient a driver's gaze. - Ho, C; Spence, C (2009)
OBJECTIVE: We report a series of three experiments designed to assess the relative speed with which people can initiate speeded head-orienting responses following the presentation of spatial warning signals. BACKGROUND: Recent cognitive neuroscience findings have shown that the human brain tends to treat stimuli occurring in peripersonal space as being somehow more behaviorally relevant and attention demanding than stimuli occurring in extrapersonal space. These brain mechanisms may be exploited in the design of warning signals. METHOD: Experiment 1 assessed the effectiveness of various different unisensory warning signals in eliciting a head-turning response to look at the potential source of danger requiring participants' immediate attention; Experiment 2 assessed the latency of a driver's responses to events occurring in the cued direction; Experiment 3 assessed the relative effectiveness of various warning signals in reorienting a person's gaze back to a central driving task while he or she was distracted by a secondary task. RESULTS: The results show that participants initiated head-turning movements and made speeded discrimination or braking responses significantly more rapidly following the presentation of a close rear auditory warning signal than following the presentation of either a far frontal auditory warning signal, a vibrotactile warning signal presented to their waist, or a peripheral visual warning signal. CONCLUSION: These results support the claim that the introduction of peripersonal warning signals results in a significant performance advantage relative to traditionally designed warnings. APPLICATION: Warning systems that have been designed around the constraints of the human brain offer great potential in the future design ofmultisensory interfaces.